Interactive Volumetric Fog System in Unreal Engine 5 Using Distance Fields and GPU Particle Simulation - Wei, Xi (Transactions on Computer Science and Intelligent Systems Research, 2025)
Real-time volumetric fog is a crucial visual effect in modern 3D environments, enhancing depth perception, atmosphere, and immersion. However, conventional fog rendering methods often lack physical accuracy and interactivity, disconnecting players and their environment. To address this issue, this study proposes an interactive volumetric fog system based on Unreal Engine 5, designed to provide realistic static fog rendering and dynamic responses to user interaction. The main objective is to create a system that simulates volumetric fog behaviour in real time while allowing the fog to adapt visually to player movement. The proposed method consists of two core modules: a physically-based volumetric material constructed using distance fields and optical attenuation principles, and a Niagara-based Graphics Processing Unit (GPU) particle system that enables fog displacement and turbulence through programmable repulsion forces. Specifically, the system uses distance-normalized falloff functions, real-time blueprint data communication, and procedural texture modulation to create seamless visual integration between static fog volume and interactive particle behaviour. This study is implemented entirely within Unreal Engine 5 using procedural data and engine-native tools. Results demonstrate that the system effectively simulates soft, immersive fog with natural gradients and dynamically responds to player position visually compellingly. Experimental evaluation confirms the feasibility of deploying this system in real-time applications requiring high atmospheric realism and interaction levels.